استراتيجية تعليم اللغة العربية في عصر العولمة - Rizal Firdaus; Kurnia Afandi Al Farisi; Robi Mandala (Universitas Yudharta Pasuruan, 2019)
Arabic is the only high language that has been valued to maintain its entity and become scientific. The book shows a correct and accurate understanding and taste only in Arabic, and the heritage books of Islamic sciences are written in that language. As time fluctuates like the ball, the situation has changed in times and in our present time human beings live in the era of globalization where western countries dominate all parts of the world and in all their fields such as the field of economy and education, the Islamic countries were affected by the entry of Western ideas, culture and traditions that lead to the weakness of the Arabic language. Therefore, teaching Arabic in the age of globalization requires a variety of and appropriate means, methods and methods, and this research aims to develop the appropriate methods and teaching strategy for teaching The Arabic language in the age of globalization, and one of the ways that can be used in the age of globalization are language games, which are designed for the purpose of Language learning, expanding or developing certain concepts to understand historical or cultural events or to help children acquire language skills through play. Language games are divided into multiple types, divided according to basic language skills, namely oral games and reading games. In this research, the authors will show about different language games that can be used in the teaching of Arabic language in the age of globalization depending on language skills, including: (1) character, word and sentence recognition games. (2) Reading training games from right to left. (3) Training games to read a word or phrase and short text. (4) Games to recognize and correct reading errors. (5) Vocabulary absorption training games, short phrases or short text.